Unravelling the mosquito-haemosporidian parasite-bird host network in the southwestern Iberian Peninsula: insights into malaria infections, mosquito community and feeding preferences - Carlos Mora-Rubio; Martina Ferraguti; Sergio Magallanes; Daniel Bravo-Barriga; Irene Hernandez-Caballero; Alfonso Marzal; Florentino de Lope (Parasites & Vectors, 2023)
Abstract Bakground Vector-borne diseases affecting humans, wildlife and livestock have significantly increased their incidence and distribution in the last decades. Because the interaction among vectors-parasite-vertebrate hosts plays a key role driving vector-borne disease transmission, the analyses of the diversity and structure of vector-parasite networks and host-feeding preference may help to assess disease risk. Also, the study of seasonal variations in the structure and composition of vector and parasite communities may elucidate the current patterns of parasite persistence and spread as well as facilitate prediction of how climate variations may impact vector-borne disease transmission. Avian malaria and related haemosporidian parasites constitute an exceptional model to understand the ecology and evolution of vector-borne diseases. However, the characterization of vector-haemosporidian parasite-bird host assemblages is largely unknown in many regions. Methods Here, we analyzed 5859 female mosquitoes captured from May to November in five localities from southwestern Spain to explore the composition and seasonal variation of the vector-parasite-vertebrate host network. Results We showed a gradual increase in mosquito abundance, peaking in July. A total of 16 different haemosporidian lineages were found infecting 13 mosquito species. Of these assemblages, more than 70% of these vector-parasite associations have not been described in previous studies. Moreover, three Haemoproteus lineages were reported for the first time in this study. The prevalence of avian malaria infections in mosquitoes varied significantly across the months, reaching a maximum in November. Mosquito blood-feeding preference was higher for mammals (62.5%), whereas 37.5% of vectors fed on birds, suggesting opportunistic feeding behavior. Conclusion These outcomes improve our understanding of disease transmission risk and help tovector control strategies. Graphical abstract